Importance of additional information, as a complement to information coming from packaging, to promote meat substitutes: A case study on a sausage based on vegetable proteins. (January 2021) - Martin, Christophe; Lange, Christine; Marette, Stéphan
Highlights: Purchase preferences (PP) based on taste alone were in favor of the meat product. Packaging induced a significant increase in the PP for the plant-based product. Health information increased in the PP and the WTP for the plant-based product. Environmental information increased in the WTP for the plant-based product. Our results militate in favor of the dissemination of additional information. Abstract: Scientific literature has shown that a partial replacement of meat-based foods with plant-based foods would be beneficial for public health and the environment. However, both lack of sensory attractiveness and lack of consumer awareness regarding benefits of rebalancing diets in favor of plant protein partially explain the low market shares for meat alternatives. In the context of a possible substitution of a meat product (pork-based sausage) by a visually very close counterpart based on vegetable proteins, the objective of this work was to study the possibility of changing consumer preferences towards the plant-based product by gradually providing information concerning the health or environmental consequences of producing and consuming both types of products. We studied consumers' preferences after a blind tasting, after a tasting in the presence of the packaging, and after the dissemination of two stages of information. The assessment of consumer preferences was carried out using purchase preferences (PP) and willingness to pay (WTP). After the blind tasting, PP were clearly oriented towards the meat product. After the tasting with packaging information, the gap between the two products narrowed, but PP were still turned towards the meat product. The dissemination of a first informative message about either health or the environment was not enough to modify consumers' WTP. Adding a second message concerning health led to an equivalence of the two products studied in terms of WTP and PP. The combination of the two environmentally informative messages also made it possible to obtain an equivalence of the WTP for both products, but the PP were still turned towards the pork product. This suggests that the impact of additional information depends on the information disseminated. Overall, these results militate in favor of the dissemination of information presenting the consequences of the consumption of meat-based or vegetable protein-based products.